Creation by programs: Report of experiences with the pedagogy of performative scenes in Cariri of Paraíba (Revista de Ensino em Artes, Moda e Design, 2026)
This report/article aims to show forms of pedagogy that intertwine performance practices with contemporary dance and theatre, in a university context and in workshops open to the public. It starts from the notion of a performative program, associating it with some conceptions and examples of play, as a teaching and creation strategy. The methodology used is action research and reflective practice, through autobiographical accounts. It is hoped to contribute to the teaching of performing and visual arts, starting from the experience with performance as a point of departure.
Keywords: performative program; game; pedagogy